Size and Shape Exclusion in 2D Silicon Dioxide Membranes. Issue 9 (15th December 2022) - Dementyev, Petr; Khayya, Neita; Zanders, David; Ennen, Inga; Devi, Anjana; Altman, Eric I.
Abstract: 2D membranes such as artificially perforated graphene are deemed to bring great advantages for molecular separation. However, there is a lack of structure‐property correlations in graphene membranes as neither the atomic configurations nor the number of introduced sub‐nanometer defects are known precisely. Recently, bilayer silica has emerged as an inherent 2D membrane with an unprecedentedly high areal density of well‐defined pores. Mass transfer experiments with free‐standing SiO2 bilayers demonstrated a strong preference for condensable fluids over inert species, and the measured membrane selectivity revealed a key role of intermolecular forces in ångstrom‐scale openings. In this study, vapor permeation measurements are combined with quantitative adsorption experiments and density functional theory (DFT) calculations to get insights into the mechanism of surface‐mediated transport in vitreous 2D silicon dioxide. The membranes are shown to exhibit molecular sieving performance when exposed to vaporous methanol, ethanol, isopropanol, and tert‐butanol. The results are normalized to the coverage of physisorbed molecules and agree well with the calculated energy barriers. Abstract : Vitreous bilayer silica is exposed toward vaporous alcohols (CH3 )N H3‐N COH (0 ≤ N ≤ 3). The substances are shown spectroscopically to populate the surface with adsorbates. Permeation measurements with free‐standing sheets demonstrate that natural pores in the 2D material are capable to discriminate molecular dimensions. The membrane selectivity is rationalized with the help of rigorous density functional theory (DFT) calculations.